2000
DOI: 10.1016/s0304-3959(99)00224-9
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and regulation of α 2-adrenoceptors in rat dorsal root ganglia

Abstract: Using in situ hybridization with riboprobes the distribution of alpha(2A)-, alpha(2B)- and alpha(2C)-adrenoceptor mRNAs were studied in normal rat dorsal root ganglia and after unilateral peripheral nerve injury (total nerve transection) or inflammation. The most common adrenoceptor mRNA was of the alpha(2C) subtype (almost 80% of all neuron profiles) followed by the alpha(2A) subtype (almost 20%), whereas alpha(2B)-adrenoceptor mRNA was only found in small numbers of neuron profiles. The most dramatic effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 59 publications
4
83
0
2
Order By: Relevance
“…In addition to the well-known location of ␣ 2 -adrenoceptors on presynaptic sympathetic nerve terminals, whose activation results in inhibition of further release of norepinephrine (51,52), there is also evidence for ␣ 2 -adrenoceptors located on sensory neurons in DRG (5,47). Functional evidence for ␣ 2 -adrenoceptors on peripheral sensory nerve endings has been demonstrated in various organs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the well-known location of ␣ 2 -adrenoceptors on presynaptic sympathetic nerve terminals, whose activation results in inhibition of further release of norepinephrine (51,52), there is also evidence for ␣ 2 -adrenoceptors located on sensory neurons in DRG (5,47). Functional evidence for ␣ 2 -adrenoceptors on peripheral sensory nerve endings has been demonstrated in various organs.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that dexmedetomidine was active on the injured side at a dose that did not aect the contralateral limb, further suggests that the injury induces adrenergic sensitivity. This may occur at the level of the ipsilateral dorsal root ganglia (DRG) and/or the spinal dorsal horn, where changes in a 2 AR expression have been described (Cho et al, 1997;Fareed et al, 1997;Birder & Perl, 1999;Stone et al, 1999;Shi et al, 2000). However, the direction of the change is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…One report indicated that a 2A AR immunoreactivity was upregulated in DRG neurons after sciatic nerve injury (Birder & Perl, 1999), but another study found evidence for downregulation in the spinal dorsal horn after nerve injury (Stone et al, 1999). Moreover, while two studies showed that mRNA for a 2A AR was reduced after spinal nerve injury (Fareed et al, 1997;Cho et al, 1997), a recent study demonstrated an increase of this subtype in DRG neurons after nerve transection (Shi et al, 2000). Nerve injury has been shown to produce a decrease in a 2C AR mRNA in DRG neurons (Cho et al, 1997), while a 2C AR immunoreactivity was unchanged or increased at the spinal cord level using a similar spinal nerve-injury model (Stone et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, mRNA for alpha 2A -adrenoceptors is up-regulated in DRG neurons after nerve lesion. 82 Clinical studies in humans support the idea that nociceptors develop catecholamine sensitivity after complete or partial nerve lesions. After limb amputation, injection of epinephrine around a stump neuroma is reported to be intensely painful.…”
Section: 65mentioning
confidence: 92%